"My happiest time" or "my saddest time"? The spatial and generational construction of marriage among youth in rural Malawi and Lesotho. Issue 2 (19th October 2017) - Ansell, Nicola; Hajdu, Flora; van Blerk, Lorraine; Robson, Elsbeth
Abstract : Marriage among African teenagers is currently a central focus of campaigns by UN agencies and international NGOs. Yet marriage has received only limited attention from geographers and has largely escaped the attention of geographers of youth. In this paper we explore the relational geographies of age that underlie young people's motivations for, and experiences of, marriage in two rural African settings with differing marriage practices: matrilocal southern Malawi and patrilocal Lesotho. We draw on participatory research activities and life history interviews conducted with 80 people aged between 10 and 24 years old. While the young people's attitudes and experiences were varied and complex, starkly different accounts emerged from the two settings. In particular, young women in Lesotho offered very negative assessments of marriage, while those in Malawi were very much more positive. Through these examples, we highlight how young people's marriage choices and experiences are relationally produced. Decisions about whether, when and whom to marry reflect socially entrenched expectations concerning generational allocations of resources, labour and responsibilities, which intersect with contemporary social and economic processes including poverty, unemployment, land scarcity and AIDS. Experiences of marriage, too, are produced through practices that are spatially structured and contextually situated in relation to socio‐economic conditions. Thus marriage, as a "vital conjuncture" in young people's lives, plays a key role in the relational construction of individual lifecourses and in (re)constructing relationships of age, gender and, especially, generation.